Identifikasi Proses Produksi Di Industri Kreatif Batik Laweyan Menggunakan Pendekatan Teknometrik - Mulyono, Nugroho Sri; , Siti Nandiroh, S.T., M.Eng; , Ratnanto Fitriadi, S.T., M.T (2015)
Batik is one of Indonesia's legacy in the field of fashion that remains famous to this day. Popularity of batik is not only famous in Indonesia, but also to foreign countries. In addition, batik is also one of the Creative Industries in Surakarta. The center of batik production in Surakarta one of them is in Laweyan. Laweyan as one of the central production of batik renowned for the quality of batik cloth produced very nice. Good quality batik cloth is inseparable from the production process that has been good. The use of technology is one of the factors of production process. In addition, environmental factors are already getting damaged to make the entire product must keep the environment, nor with batik production process that still must maintain an Environmental. This study aims to identify the processes of production and green production system that has been implemented in Kampoeng Batik Laweyan Development Forum as the container industry owners batik in Laweyan. In addition, this study also conducted to determine the level of application of the technology in the community. Results of the study, showed that the entire industry producing batik cloth by using equipment that is still manual, such as beautiful, cap, and valet. In addition, of the 12 industries studied batik almost the entire industry has been implementing green production system such as using natural raw materials, recycling of production waste, and the use of wastewater as part of efforts to maintain the environment, especially the river environment. Also based on the calculation technometric, it is known that all kinds of batik included into the category of semi-modern with TCC value for batik is 0.578, TCC to batik is 0.573, and the TCC for batik printing is 0.578.